Do mutual fund managers beat the market? Evidence from the Johannesburg stock exchange - Kunene, Thembumenzi Phinda (My University, 2017)
South Africa has been mirroring the global increase in investments made in mutual funds. This rise in assets managed by mutual fund managers has been coupled with rising curiosity among investors, as to whether fund managers are able to outperform the market. The rising curiosity of investors has been translated into a wide debate in literature documented since the early days of Treynor (1965), Sharpe (1966) and Jensen (1968), and most recently Bradfield and Swartz (2001) and Nana (2012). This study adds to the existing literature by using top ten performing equity unit trusts in South Africa. In particular, three questions are asked; (a) are there any fund characteristics that influence fund performance? (b) is there evidence of persistence in performance of funds? (c) do mutual fund managers beat the market? Regression analysis and Jensen’s CAPM model are employed to answer the three questions. The results of this study are therefore three fold. Firstly, it is found that fund risk, find size and fund age have no effect on mutual fund performance. Secondly, evidence of weak short-term persistence is found, since for all of the funds under investigation persistence does not happen regularly. Lastly, and more importantly, the top ten performing equity unit trusts over the decade ranging from January 2006 to December 2015 are able to outperform the market, as represented by the Johannesburg Stock Exchange All Share Index (JSE ALSI). These unit trusts produce superior or abnormal returns which are approximately 0.47% more than that produced by the market. We argue that such marginal outperformance might just be a mere representation of superior skills possessed by the selected fund managers and cannot be extended to the entire South African unit trust industry.
Thesis submitted in Fulfilment of the requirements for the Degree of Master of Management in Finance and Investment at Wits Business School Faculty of Commerce, Law and Management University of the Witwatersrand 27 February 2017